Mini review: Hyperglycemia in ischemic stroke - Honglian Duan; Wesley Kohls; Roxanne Ilagan; Xiaokun Geng; Yuchuan Ding (Wolters Kluwer Medknow Publications, 2022)
The impact of stroke, currently the second leading cause of death worldwide, continues to worsen, and even those that survive can have persistent neurological deficits. A potentially significant implication may be due to hyperglycemia, found in one-third of all acute ischemic stroke (AIS) patients. However, prior studies reported conflicting information about the impact of hyperglycemia on poststroke prognosis, likely due to different measurements of stress-induced hyperglycemia. The glucose-to-glycated hemoglobin ratio is an index of stress-induced hyperglycemia after AIS that better quantifies acute changes in blood glucose, as opposed to absolute variations in glucose levels. Moderate blood glucose reductions might counteract the negative effects of hyperglycemia and glycemic control medications can also play a role in neuroprotection. The liver is the main organ that functions to maintain energy and glucose metabolism and the effects of AIS can reach far peripheral organs, including the liver. In this review, we highlighted the mechanism responsible for acute poststroke hyperglycemia, a hepatic inflammatory pathway that results in hepatic gluconeogenesis and reduced hepatic insulin sensitivity. Hepatitis cascades lead to hepatic gluconeogenesis, and targeted therapy with antihyperglycemic drugs has the potential to improve stroke prognosis and recovery.